Technologický proces součásti "hydraulický válec" - Cejpek, Petr (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2013)
Předmětem této bakalářské práce je rozbor technologického procesu výroby součásti ‘‘hydraulický válec‘‘ v podmínkách firmy S&K TOOLS spol. s r. o. V úvodu práce je proveden rozbor stávajícího technologického procesu. Cílem této práce je nalezení slabých míst výroby, sestavení návrhu na zlepšení a provedení praktického experimentu v konkrétních podmínkách firmy. V závěru je provedeno technicko-ekonomické zhodnocení.

The subject of this bachelor thesis is the analysis of technological process of manufacturing of the part called hydraulic cylinder in conditions of company S&K TOOLS spol. s r. o. There is an analysis of the present technological process in the beginning of the thesis. The main goal of this task is to find weak spots of manufacturing, create an improvement proposals and realization of practical experiment in concrete conditions of the company. Last part of the thesis is focused on realization of technical and economical evaluation.
Technological design of part "hydraulic cylinder"
Keywords: výrobní proces; technologický postup; obrábění; vrták; Mazatrol; manufacturing process; technological procedure; machining; drill bit; Mazatrol